Glucocorticoid-induced tumour necrosis factor receptor family-related protein (GITR) drives atherosclerosis in mice and is associated with an unstable plaque phenotype and cerebrovascular events in humans. (30th July 2020) - Shami, Annelie; Atzler, Dorothee; Bosmans, Laura A; Winkels, Holger; Meiler, Svenja; Lacy, Michael; van Tiel, Claudia; Ta Megens, Remco; Nitz, Katrin; Baardman, Jeroen; Kusters, Pascal; Seijkens, Tom; et al.
Abstract: Aims: GITR—a co-stimulatory immune checkpoint protein—is known for both its activating and regulating effects on T-cells. As atherosclerosis bears features of chronic inflammation and autoimmunity, we investigated the relevance of GITR in cardiovascular disease (CVD). Methods and results: GITR expression was elevated in carotid endarterectomy specimens obtained from patients with cerebrovascular events ( n  = 100) compared to asymptomatic patients ( n  = 93) and correlated with parameters of plaque vulnerability, including plaque macrophage, lipid and glycophorin A content, and levels of interleukin (IL)-6, IL-12, and C-C-chemokine ligand 2. Soluble GITR levels were elevated in plasma from subjects with CVD compared to healthy controls. Plaque area in 28-week-old Gitr −/− Apoe −/− mice was reduced, and plaques had a favourable phenotype with less macrophages, a smaller necrotic core and a thicker fibrous cap. GITR deficiency did not affect the lymphoid population. RNA sequencing of Gitr −/− Apoe −/− and Apoe −/− monocytes and macrophages revealed altered pathways of cell migration, activation, and mitochondrial function. Indeed, Gitr −/− Apoe −/− monocytes displayed decreased integrin levels, reduced recruitment to endothelium, and produced less reactive oxygen species. Likewise, GITR-deficient macrophages produced less cytokines and had a reduced migratory capacity. Conclusion: Our data reveal a novel role for the immune checkpoint GITR in driving myeloid cell recruitment and activation in atherosclerosis, thereby inducing plaque growth and vulnerability. In humans, elevated GITR expression in carotid plaques is associated with a vulnerable plaque phenotype and adverse cerebrovascular events. GITR has the potential to become a novel therapeutic target in atherosclerosis as it reduces myeloid cell recruitment to the arterial wall and impedes atherosclerosis progression. Graphical Abstract: